The effects of feed additives, sodium metabisulfite and processing conditions on nursery pigs fed diets containing deoxynivalenol; and the impact of feed withdrawal and diet blending on finishing pig growth, carcass composition and economics - Frobose, Hyatt Lowell (Kansas State University, 2012)
Thirteen experiments using a total of 7,589 nursery and finishing pigs were conducted to evaluate the effects of deoxynivalenol (DON), feed additives and processing conditions on nursery pig growth performance. In addition, feed withdrawal and diet blending were evaluated in finishing pigs. Experiment 1 tested 3 feed additives in DON-contaminated diets with only Defusion Plus improving performance. Experiment 2 evaluated Biofix in both low- and high-DON diets and showed no effects on growth. Experiments 3 and 4 further evaluated levels of Defusion and the effects of pelleting and supplemental nutrients in DON-contaminated diets. Defusion improved growth in low-DON diets, but had variable effects in high DON diets. Pelleting DON-contaminated diets resulted in comparable growth to pigs fed positive control diets in meal form. In Exp. 5 and 6, pilot studies evaluated DON-detoxification using sodium metabisulfite (SMB) with hydrothermal treatment in both an autoclave and a pellet mill. These conditions reduced analyzed DON by as much as 89 and 75% for the autoclave and pellet mill, respectively. In Exp. 7 and 8, pelleting DON-contaminated diets with SMB improved growth. Experiments 9 and 10 evaluated feed-withdrawal time on carcass composition and economic returns. These experiments showed that pre-slaughter fasting for up to 36 h prior can be used to avoid weight discounts in heavyweight pigs without negatively impacting carcass composition and maintaining overall revenue. However, these advantages come with a potential reduction in carcass weight and increased incidence of leaking ingesta, which can result in condemned heads. Experiments 11, 12, and 13 compared phase-feeding to blending diets using an automated feed delivery system. These studies showed that corn-supplement blending is not economical and feeding diets blended to a Lys curve results in lower feed costs compared to phase-feeding, but due to reductions in growth and carcass weight, these savings do not translate into higher income over feed cost. Finally, Exp. 13 showed that over- and under-budgeting situations do not significantly influence overall returns, but pigs fed under-budgeted diets performed more closely to those fed correctly estimated feed budgets.
Keywords: Deoxynivalenol; Nursery pigs; Sodium metabisulfite; Feed blending; Feed withdrawal; Finishing pigs; Animal Sciences (0475)